Supply network position and firm performance: evidence from Chinese listed manufacturing companies - Shi, Jinyan; Yang, Jiangheng; Li, Yanxi (Journal of Business Economics and Management, 2019)
The aim of this paper is to examine the relationship between supply network position and firm performance. A-share manufacturing companies listed from 2013 to 2015 are chosen as the initial samples, and large sample supply networks are constructed with relational embeddedness and structural embeddedness. The location of supply network is depicted by network centrality and structural hole with social network analysis, and the influence of supply network position on the corporate performance is examined with multiple OLS regression analysis. This paper observes that a firms’ supply network position is an important factor affecting its performance. The higher the network centrality is, the richer the structural holes are, and the worse the company’s performance is. The results suggest that firms that have a high level of centrality or rich structural holes in their supply networks will gain limited information, resource and control benefits and face great business risks that may negatively influence their performance.